Pengembangan Buku Ajar Layanan Prima dengan Pendekatan Search, Solve, Create, Share (SSCS) untuk Memberdayakan Kemampuan Berpikir Kritis Mahasiswa - Veni Rafida (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
This study aims to develop a comprehensive service excellence textbook based on the Search, Solve, Create, and Share (SSCS) model to significantly enhance university students’ critical thinking skills. The research employed a Research and Development (R&D) method using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. Research instruments included initial needs analysis, validation sheets from content, design, and language experts, student response questionnaires, as well as pretest and posttest instruments to specifically measure critical thinking skills. The results indicate that the SSCS-based service excellence textbook is highly feasible for use, as validated by experts with a very good category. Limited field testing also revealed positive student responses and a measurable improvement in students’ critical thinking abilities after using the textbook. Therefore, the developed SSCS-based textbook is highly effective as an innovative learning resource that seamlessly integrates theory and practice, while strongly supporting student-centered learning environments.